An aluminum alloy powder for additive manufacturing and a method of manufacturing the same

CN122898769BActive Publication Date: 2026-11-06ANHUI ZHONGTI NEW MATERIAL TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611394536.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-09-09
Publication Date
2026-11-06
Estimated Expiration
2046-09-09

AI Technical Summary

Technical Problem

虽然,Al-Si系合金中Si含量的提升使其改善耐磨性,但是同步劣化了其延展性、高温承载能力及导电导热性等性能,而且在激光粉末床熔融工艺中,Al-Si系合金成形过程还存在凝固开裂、力学各项异性等缺陷

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The application discloses an aluminum alloy powder for additive manufacturing and a preparation method thereof, and belongs to the technical field of additive manufacturing, and comprises the following components in percentage by mass: Si 12.0-13.3%, Mg 0.8-1.5%, Cu 1.5-2.3%, Ti 0.42-0.57%, Y 0.2-0.32%, Sc 0.18-0.25%, Zr 0.08-0.12%, V 0.06-0.12%, B4C powder 0.18-0.29%, graphite powder 0.25-0.43%, and the balance of Al and inevitable impurities; and the total carbon content is 0.3-0.47%. The aluminum alloy powder for additive manufacturing improves the Si content, endows the aluminum alloy with the wear resistance advantage, improves the ductility, high-temperature bearing capacity and other characteristics of the aluminum alloy, and effectively inhibits the LPBF process defects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to an aluminum alloy powder for additive manufacturing and its preparation method, belonging to the field of additive manufacturing technology. Background Technology

[0002] Aluminum alloys, as high-strength, lightweight, and machinable materials, play a crucial role in industry and are widely used in construction, automotive, shipbuilding, and aerospace fields. Al-Si alloys are among the most commonly used metal powder materials in laser powder bed melting processes. Extensive research has confirmed that the wear resistance of Al-Si alloys increases monotonically with increasing Si content. When the Si content exceeds the eutectic composition (11.7 wt.%), hard Si particles are distributed in a fine, dispersed state within the soft α-Al matrix, effectively undertaking the functions of load transfer and crack propagation inhibition during the wear process. Although increasing the Si content in Al-Si alloys improves their wear resistance, it simultaneously degrades their ductility, high-temperature load-bearing capacity, and electrical and thermal conductivity. Furthermore, in laser powder bed melting processes, Al-Si alloys also suffer from defects such as solidification cracking and mechanical anisotropy during forming. Summary of the Invention

[0003] At least to address one of the problems existing in the prior art, the present invention provides an aluminum alloy powder for additive manufacturing and a method for preparing the same, which improves the wear resistance of aluminum alloys by increasing the Si content, while also enhancing their ductility, high-temperature load-bearing capacity and other properties, and effectively suppressing defects in the LPBF process.

[0004] To achieve the above objectives, the present invention adopts the following technical solution: an aluminum alloy powder for additive manufacturing, comprising, by mass percentage: Si 12.0~13.3%, Mg 0.8~1.5%, Cu 1.5~2.3%, Ti 0.42~0.57%, Y 0.2~0.32%, Sc 0.18~0.25%, Zr 0.08~0.12%, V 0.06~0.12%, B4C powder 0.18~0.29%, graphite powder 0.25~0.43%, with the balance being Al and unavoidable impurities.

[0005] Preferably, the total mass of carbon in the B4C powder and carbon in the graphite powder is 0.3~0.47% of the mass of the aluminum alloy powder.

[0006] Preferably, the total mass percentage of Mg to the total mass of Cu is ≥55%.

[0007] Preferably, the mass ratio of total Y, total Zr and total V is 2.5:1:1.

[0008] Preferably, the mass ratio of total Ti, total Sc, total Y to total Zr is 5:2:2.5:1.

[0009] Preferably, the mass ratio of total Cu to total Y is 7~8:1.

[0010] Preferably, the B4C powder has a particle size of 200~500nm.

[0011] Preferably, the graphite powder has a particle size of 1~5μm.

[0012] This invention provides a method for preparing aluminum alloy powder for additive manufacturing. Pure Al ingots, Al-Si, Al-Cu, Al-Mg, Al-Ti, Al-Y, Al-Sc, Al-Zr, and Al-V master alloys are heated and mechanically stirred to melt under an inert gas. B4C powder and graphite powder are then added, and the mixture is stirred and dispersed uniformly using a combination of mechanical and electromagnetic stirring. The mixture is then electromagnetically stirred and kept at a constant temperature to obtain a uniform melt. Finally, the melt is atomized by gas and dried to obtain aluminum alloy powder for additive manufacturing.

[0013] Preferably, the method for preparing the aluminum alloy powder for additive manufacturing specifically includes the following steps; (1) Pure Al ingots, Al-Si, Al-Cu, Al-Mg, Al-Ti, Al-Y, Al-Sc, Al-Zr, and Al-V master alloys are added to the melting crucible according to the above-mentioned element mass percentages; (2) Inert gas is introduced into the melting crucible to form a protective atmosphere. The melting crucible is then heated to 730~750℃ and mechanically stirred to melt the pure Al ingot and all intermediate alloys. B4C powder and graphite powder are then added while mechanically stirring, and electromagnetic stirring is turned on for 10~15 minutes to disperse them evenly. The mechanical stirring is then turned off, and electromagnetic stirring is continued for 5~10 minutes to obtain a uniform melt. (3) The uniform melt is transferred into the intermediate ladle crucible under an inert gas atmosphere, and then flows into the atomization chamber through the zirconia guide tube. At the same time, high-pressure inert gas is injected for atomization and powder making. The airflow is classified to obtain powder with a size of 15~53μm. The powder is dried with inert gas to obtain aluminum alloy powder for additive manufacturing.

[0014] Preferably, the mechanical stirring speed is 300~500 rpm.

[0015] Preferably, the frequency of the electromagnetic stirring is 50~100Hz.

[0016] Preferably, a zirconia ceramic filter screen is provided inside the intermediate ladle crucible.

[0017] Preferably, the inert gas is argon or helium with a purity of 99.999%.

[0018] Preferably, the pressure of the high-pressure inert gas is 2.5~4.0 MPa.

[0019] The beneficial effects of this invention are as follows: The aluminum alloy powder of this invention uses near-eutectic high Si as the formability basis, and is strengthened by appropriate amounts of Mg, Cu, Sc, Zr, Ti, B4C, Y, and V multi-element synergistic reinforcement, which refines the grains, reduces solidification stress concentration, and effectively improves the strength, ductility, and high-temperature load-bearing capacity of the aluminum alloy material. The aluminum alloy powder of this invention, through the synergistic effect of appropriate amounts of Ti, Y, Zr, V and other elements with other elements, and by controlling an appropriate amount of carbon content, can significantly suppress hot cracking, reduce crack sensitivity, improve additive manufacturing processes such as LPBF, and effectively avoid defects such as solidification cracking and mechanical anisotropy in the alloy. At the same time, the components of the aluminum alloy powder also endow the aluminum alloy with excellent wear resistance. Detailed Implementation

[0020] The following is a clear and complete description of the technical solutions in the implementation of this invention. The described embodiments are only a part of the embodiments of this invention, and not all of them. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this invention. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents, instruments, or components used that do not specify the manufacturer are all conventional products that can be purchased commercially.

[0021] The inert gas used in this invention is argon or helium with a purity of 99.999%.

[0022] The selection of Al-Si, Al-Cu, Al-Mg, Al-Ti, Al-Y, Al-Sc, Al-Zr, Al-Ni, Al-V, and Al-Mn master alloys used is shown in Table 1.

[0023] Table 1. Composition of master alloys

[0024] Example 1 An aluminum alloy powder for additive manufacturing and its preparation method, comprising, by mass percentage: Si 12.0%, Mg 0.8%, Cu 1.5%, Ti 0.51%, Y 0.2%, Sc 0.18%, Zr 0.12%, V 0.06%, B4C powder 0.18%, graphite powder 0.43%, with the balance being Al and unavoidable impurities; wherein, the total carbon content is approximately 0.469%, the total Mg content accounts for 53.33% of the total Cu content by mass; the mass ratio of total Y, total Zr to total V is 10:6:3, the mass ratio of total Ti, total Sc, total Y to total Zr is approximately 4.25:1.5:1.67:1, and the mass ratio of total Cu to total Y is 7.5:1; The specific steps for preparing the aluminum alloy powder are as follows: (1) Pure Al ingots, Al-Si, Al-Cu, Al-Mg, Al-Ti, Al-Y, Al-Sc, Al-Zr, and Al-V master alloys are added to the melting crucible according to the above-mentioned element mass percentages; (2) Argon gas is introduced into the melting crucible to form a protective atmosphere. The melting crucible is then heated to 750°C and mechanically stirred at 400 rpm to melt the pure Al ingot and all intermediate alloys. B4C powder and graphite powder are added while mechanically stirring. Electromagnetic stirring is turned on and the mixture is stirred at 80 Hz for 12 minutes to disperse it evenly. Mechanical stirring is turned off and the mixture is stirred at 80 Hz for 8 minutes to obtain a uniform melt. (3) The uniform melt is transferred into an intermediate ladle crucible containing a zirconia ceramic filter screen (pore size 10ppi) under an argon atmosphere, and then flows into the atomization chamber through a zirconia guide tube. At the same time, high-pressure argon gas at a pressure of 3.8Mpa is injected for atomization and powdering. The gas flow is classified to obtain powder with a size of 15~53μm. Then, it is dried in an argon atmosphere at a temperature of 110℃ for 25min, and then cooled in an argon atmosphere to obtain aluminum alloy powder for additive manufacturing.

[0025] Example 2 An aluminum alloy powder for additive manufacturing and its preparation method, comprising, by mass percentage: Si 12.6%, Mg 1.2%, Cu 1.9%, Ti 0.57%, Y 0.26%, Sc 0.22%, Zr 0.1%, V 0.12%, B4C powder 0.24%, graphite powder 0.34%, with the balance being Al and unavoidable impurities; wherein, the total carbon content is approximately 0.392%, the total Mg content accounts for 63.16% of the total Cu content by mass; the mass ratio of total Y, total Zr to total V is 13:5:6, the mass ratio of total Ti, total Sc, total Y to total Zr is approximately 5.7:2.2:2.6:1, and the mass ratio of total Cu to total Y is approximately 7.3:1; The preparation method of the aluminum alloy powder is the same as that in Example 1.

[0026] Example 3 An aluminum alloy powder for additive manufacturing and its preparation method, comprising, by mass percentage: Si 13.3%, Mg 1.5%, Cu 2.3%, Ti 0.42%, Y 0.32%, Sc 0.25%, Zr 0.08%, V 0.09%, B4C powder 0.29%, graphite powder 0.25%, with the balance being Al and unavoidable impurities; wherein, the total carbon content is approximately 0.313%, the total Mg content accounts for 65.22% of the total Cu content by mass; the mass ratio of total Y, total Zr to total V is 4:1:1.125, the mass ratio of total Ti, total Sc, total Y to total Zr is approximately 5.25:3.125:4:1, and the mass ratio of total Cu to total Y is approximately 7.2:1; The preparation method of the aluminum alloy powder is the same as that in Example 1.

[0027] Example 4 An aluminum alloy powder for additive manufacturing and its preparation method, comprising, by mass percentage: Si 12.4%, Mg 1%, Cu 1.75%, Ti 0.48%, Y 0.22%, Sc 0.195%, Zr 0.088%, V 0.088%, B4C powder 0.22%, graphite powder 0.38%, with the balance being Al and unavoidable impurities; wherein, the total carbon content is approximately 0.428%, the total Mg content accounts for 57.14% of the total Cu content by mass; the mass ratio of total Y, total Zr to total V is 2.5:1:1, the mass ratio of total Ti, total Sc, total Y to total Zr is approximately 5.45:2.22:2.5:1, and the mass ratio of total Cu to total Y is approximately 7.95:1; The preparation method of the aluminum alloy powder is the same as that in Example 1.

[0028] Example 5 An aluminum alloy powder for additive manufacturing and its preparation method, comprising, by mass percentage: Si 12.8%, Mg 1.2%, Cu 2%, Ti 0.48%, Y 0.24%, Sc 0.24%, Zr 0.096%, V 0.096%, B4C powder 0.26%, graphite powder 0.25%, with the balance being Al and unavoidable impurities; wherein, the total carbon content is approximately 0.307%, the total Mg content accounts for 60.0% of the total Cu content by mass; the mass ratio of total Y, total Zr to total V is 2.5:1:1, the mass ratio of total Ti, total Sc, total Y to total Zr is approximately 5:2.5:2.5:1, and the mass ratio of total Cu to total Y is approximately 8.33:1; The preparation method of the aluminum alloy powder is the same as that in Example 1.

[0029] Example 6 An aluminum alloy powder for additive manufacturing and its preparation method, comprising, by mass percentage: Si 13%, Mg 1%, Cu 1.8%, Ti 0.5%, Y 0.25%, Sc 0.2%, Zr 0.1%, V 0.1%, B4C powder 0.26%, graphite powder 0.32%, with the balance being Al and unavoidable impurities; wherein, the total carbon content is approximately 0.377%, the total Mg content accounts for 55.6% of the total Cu content by mass; the mass ratio of total Y, total Zr to total V is 2.5:1:1, the mass ratio of total Ti, total Sc, total Y to total Zr is approximately 5:2:2.5:1, and the mass ratio of total Cu to total Y is approximately 7.2:1; The preparation method of the aluminum alloy powder is the same as that in Example 1.

[0030] Example 7 An aluminum alloy powder for additive manufacturing and its preparation method, comprising, by mass percentage: Si 12.5%, Mg 0.85%, Cu 1.7%, Ti 0.45%, Y 0.225%, Sc 0.18%, Zr 0.09%, V 0.09%, B4C powder 0.25%, graphite powder 0.36%, with the balance being Al and unavoidable impurities; wherein, the total carbon content is approximately 0.414%, the total Mg accounts for 50% of the total Cu by mass; the mass ratio of total Y, total Zr to total V is 2.5:1:1, the mass ratio of total Ti, total Sc, total Y to total Zr is approximately 5:2:2.5:1, and the mass ratio of total Cu to total Y is approximately 7.56:1; The preparation method of the aluminum alloy powder is the same as that in Example 1.

[0031] Example 8 An aluminum alloy powder for additive manufacturing and its preparation method, comprising, by mass percentage: Si 12.2%, Mg 0.8%, Cu 1.55%, Ti 0.46%, Y 0.23%, Sc 0.184%, Zr 0.092%, V 0.092%, B4C powder 0.36%, graphite powder 0.32%, with the balance being Al and unavoidable impurities; wherein, the total carbon content is approximately 0.377%, the total Mg content accounts for 51.61% of the total Cu content by mass; the mass ratio of total Y, total Zr to total V is 2.5:1:1, the mass ratio of total Ti, total Sc, total Y to total Zr is approximately 5:2:2.5:1, and the mass ratio of total Cu to total Y is approximately 6.74:1; The preparation method of the aluminum alloy powder is the same as that in Example 1.

[0032] Comparative Example 1 An aluminum alloy powder for additive manufacturing and its preparation method differ from Example 1 in that: by mass percentage, it comprises: Si 12.0%, Mg 0.8%, Cu 1.5%, Ti 0.51%, Y 0.2%, Sc 0.18%, Zr 0.12%, V 0.06%, B4C powder 0.21%, graphite powder 0.43%, with the balance being Al and unavoidable impurities, and the total carbon content is approximately 0.477%; the rest are the same.

[0033] Comparative Example 2 An aluminum alloy powder for additive manufacturing and its preparation method differ from Example 1 in that: by mass percentage, it comprises: Si 12.0%, Mg 0.8%, Cu 1.5%, Ti 0.51%, Y 0.2%, Sc 0.18%, Zr 0.12%, V 0.06%, B4C powder 0.18%, graphite powder 0.25%, with the balance being Al and unavoidable impurities, and the total carbon content is approximately 0.289%; the rest are the same.

[0034] Comparative Example 3 An aluminum alloy powder for additive manufacturing and its preparation method differ from Example 1 in that: by mass percentage, it comprises: Si 12.0%, Mg 0.8%, Cu 1.5%, Ti 0.51%, Y 0.2%, Sc 0.18%, Zr 0.12%, V 0.06%, B4C powder 0.28%, graphite powder 0.43%, with the balance being Al and unavoidable impurities, and the total carbon content is approximately 0.491%; the rest are the same.

[0035] Comparative Example 4 An aluminum alloy powder for additive manufacturing and its preparation method differ from Example 1 in that: by mass percentage, it comprises: Si 12.0%, Mg 0.8%, Cu 1.5%, Ti 0.51%, Y 0.2%, Sc 0.18%, Zr 0.12%, V 0.06%, B4C powder 0.1%, graphite powder 0.26%, with the balance being Al and unavoidable impurities, and the total carbon content is approximately 0.282%; the rest are the same.

[0036] Comparative Example 5 An aluminum alloy powder for additive manufacturing and its preparation method differ from Example 1 in that: by mass percentage, it comprises: Si 12.0%, Mg 0.7%, Cu 2.5%, Ti 0.51%, Y 0.2%, Sc 0.18%, Zr 0.12%, V 0.06%, B4C powder 0.18%, graphite powder 0.43%, with the balance being Al and unavoidable impurities; the rest are the same.

[0037] Comparative Example 6 An aluminum alloy powder for additive manufacturing and its preparation method differ from Example 1 in that: by mass percentage, it comprises: Si 12.0%, Mg 0.8%, Cu 1.5%, Ti 0.51%, Y 0%, Sc 0.38%, Zr 0.12%, V 0.06%, B4C powder 0.18%, graphite powder 0.43%, with the balance being Al and unavoidable impurities; the rest are the same.

[0038] Comparative Example 7 An aluminum alloy powder for additive manufacturing and its preparation method differ from Example 1 in that: by mass percentage, it comprises: Si 12.0%, Mg 0.8%, Cu 1.5%, Ti 0.51%, Y 0.38%, Sc 0%, Zr 0.12%, V 0.06%, B4C powder 0.18%, graphite powder 0.43%, with the balance being Al and unavoidable impurities; the rest are the same.

[0039] Comparative Example 8 An aluminum alloy powder for additive manufacturing and its preparation method differ from Example 1 in that: by mass percentage, it comprises: Si 12.0%, Mg 0.8%, Cu 1.5%, Ti 0.25%, Y 0.2%, Sc 0.18%, Zr 0.12%, V 0%, B4C powder 0.18%, graphite powder 0.43%, with the balance being Al and unavoidable impurities; the rest are the same.

[0040] Comparative Example 9 An aluminum alloy powder for additive manufacturing and its preparation method differ from Example 1 in that: by mass percentage, it comprises: Si 12.0%, Mg 1.8%, Cu 1%, Ti 0.42%, Y 0%, Sc 0.35%, Zr 0.12%, V 0%, B4C powder 0.18%, graphite powder 0.23%, with the balance being Al and unavoidable impurities; an Al-Mn intermediate is added during melt preparation; the rest are the same.

[0041] Comparative Example 10 An aluminum alloy powder for additive manufacturing and its preparation method differ from Example 1 in that the preparation method of the aluminum alloy powder comprises the following steps: (1) Pure Al ingots, Al-Si, Al-Cu, Al-Mg, Al-Ti, Al-Y, Al-Sc, Al-Zr, and Al-V master alloys are added to the melting crucible according to the above-mentioned element mass percentages; (2) Argon gas is introduced into the melting crucible to form a protective atmosphere, and then the melting crucible is heated to 750°C to melt the pure Al ingot and all intermediate alloys. The temperature is maintained for 20 minutes, and electromagnetic stirring is performed every 5 minutes. Electromagnetic stirring is performed at a frequency of 80 Hz for 5 minutes to obtain a uniformly dispersed melt. (3) The melt is transferred into the intermediate ladle crucible containing a zirconia ceramic filter under an argon atmosphere, and then flows into the atomization chamber through the zirconia guide tube. At the same time, high-pressure argon gas with a pressure of 3.8 MPa is injected for atomization and powdering. The airflow is classified to obtain the first powder of 15~53 μm. (4) The first powder, B4C powder with a particle size of 200~500nm and graphite powder with a particle size of 1~5μm are mixed according to the above mass percentages, moistened with anhydrous ethanol, wet ball milled at 60rpm for 25min, vacuum dried at 80℃ and vacuum <1Pa for 4h, dry ball milled at 120rpm in an argon atmosphere for 70min, and then dried in an argon atmosphere at 110℃ for 25min, and then cooled in an argon atmosphere to obtain aluminum alloy powder for additive manufacturing.

[0042] Example 1: The aluminum alloy powders obtained from Examples 1-8 and Comparative Examples 1-10 were tested for oxygen content, average sphericity, flowability, loose density, tap density and void ratio according to GB / T 44239-2024 "Aluminum Alloy Powder for Additive Manufacturing". The performance results of the aluminum alloy powders are shown in Table 1.

[0043] Table 1 Properties of Aluminum Alloy Powder

[0044] As shown in Table 1, the aluminum alloy powder prepared in the embodiments of the present invention has a high degree of spherical shape, low oxygen content, good particle solidity, and relatively smooth particle surface. It has good powder flowability and packing density, which significantly improves the powder quality and greatly enhances the uniformity of subsequent laser powder spreading.

[0045] Example 2: The aluminum alloy powders obtained in Examples 1-8 and Comparative Examples 1-10 were used for printing using the LPBF process. The process parameters were: laser power 300W, laser scanning rate 1000mm / s, layer thickness 30μm, and scanning spacing 100μm. Post-solution and aging treatment was performed at: solution temperature 500℃, holding time 30min, aging temperature 180℃, and holding time 2h. The performance of the printed aluminum alloy parts was tested, and the results are shown in Table 2. Wear resistance: The coefficient of friction and wear were tested according to GB / T 12444-2006 "Test Methods for Wear of Metallic Materials - Test Ring-Block Sliding Wear Test"; Anisotropy test: Tensile specimens were prepared from the processed printed part along the additive manufacturing direction (longitudinal) and perpendicular to the additive manufacturing direction (transverse); the room temperature tensile test was conducted according to GB / T228.1-2021 to test the tensile strength. Elongation test: The elongation of the printed parts was tested according to GB / T228.1-2021; High temperature load-bearing capacity: Tensile tests were conducted in accordance with GB / T 2039-2012 to test the tensile strength at 200℃ and the tensile strength at 300℃.

[0046] The microstructure cracking was observed from the longitudinal section metallographic micrograph and the cross section metallographic micrograph.

[0047] Table 2 Performance of Aluminum Alloy Printed Parts

[0048] " / " indicates no data. Because the tensile strength at 200℃ is low, the tensile strength at 300℃ was not measured.

[0049] As shown in Table 2, compared with the comparative example, the aluminum alloy powder prepared in this embodiment of the invention, based on near-eutectic high Si as the formability foundation, with appropriate amounts of Ti, Y, Zr, V and other elements working synergistically with each other, combined with the self-lubricating assistance of graphite powder, and with controlled carbon content, can improve the fluidity and powder spreading uniformity of the aluminum alloy powder, improve the wettability of the molten pool, effectively suppress spheroidization defects, and significantly suppress hot cracking and reduce crack sensitivity through LPBF printing. The obtained aluminum alloy printed parts have a dense and uniform microstructure, are free of crack defects, and have a longitudinal tensile strength to transverse tensile strength ratio of less than 1.015. All mechanical properties are excellent. The close proximity improves additive manufacturing processes such as LPBF, effectively avoiding defects such as solidification cracking and mechanical anisotropy in alloys. At the same time, appropriate amounts of multi-element composites such as Mg, Cu, Sc, Zr, Ti, B4C, Y, and V refine the grain size and reduce solidification stress concentration. This results in aluminum alloy printed parts with a tensile strength higher than 585 MPa and an elongation higher than 8.5% at room temperature, a tensile strength higher than 390 MPa at 200℃ and a tensile strength higher than 285 MPa at 300℃. This effectively improves the strength, ductility, and high-temperature load-bearing capacity of aluminum alloy materials, while also ensuring that the aluminum alloy printed parts have excellent wear resistance.

[0050] In summary, this invention utilizes the increased Si content to impart wear resistance to aluminum alloys while simultaneously improving their ductility, high-temperature load-bearing capacity, and other properties, and effectively suppresses LPBF process defects.

[0051] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the invention can be implemented in other specific forms without departing from its spirit and essential characteristics. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description. Thus, it is intended that all variations falling within the meaning and scope of equivalents of the claims be included within the present invention.

[0052] Furthermore, it should be understood that although this specification describes embodiments, not every embodiment contains only one independent technical solution. This narrative style is merely for clarity. Those skilled in the art should consider the specification as a whole, and the technical solutions in each embodiment can also be appropriately combined to form other embodiments that can be understood by those skilled in the art.

Claims

1. An aluminum alloy powder for additive manufacturing, characterized in that, The composition, by mass percentage, includes: Si 12.0~13.3%, Mg 0.8~1.5%, Cu 1.5~2.3%, Ti 0.42~0.57%, Y 0.2~0.32%, Sc 0.18~0.25%, Zr 0.08~0.12%, V 0.06~0.12%, B4C powder 0.18~0.29%, graphite powder 0.25~0.43%, with the balance being Al and unavoidable impurities; and the total mass of carbon in the B4C powder and carbon in the graphite powder is 0.3~0.47% of the mass of the aluminum alloy powder.

2. The aluminum alloy powder for additive manufacturing according to claim 1, characterized in that, The total Mg content accounts for ≥55% of the total Cu content by mass.

3. The aluminum alloy powder for additive manufacturing according to claim 1, characterized in that, The mass ratio of the total Y, total Zr and total V is 2.5:1:

1.

4. The aluminum alloy powder for additive manufacturing according to claim 1, characterized in that, The mass ratio of the total Ti, total Sc, total Y to the total Zr is 5:2:2.5:

1.

5. The aluminum alloy powder for additive manufacturing according to claim 1, characterized in that, The mass ratio of the total Cu to the total Y is 7~8:

1.

6. The aluminum alloy powder for additive manufacturing according to claim 1, characterized in that, The B4C powder has a particle size of 200~500nm; the graphite powder has a particle size of 1~5μm.

7. A method for preparing aluminum alloy powder for additive manufacturing according to any one of claims 1 to 6, characterized in that, Pure Al ingots, Al-Si, Al-Cu, Al-Mg, Al-Ti, Al-Y, Al-Sc, Al-Zr, and Al-V master alloys are heated and mechanically stirred to melt under an inert gas atmosphere. B4C powder and graphite powder are then added, and the mixture is stirred and dispersed uniformly using a combination of mechanical and electromagnetic stirring. The mixture is then held at a constant temperature by electromagnetic stirring to obtain a homogeneous melt. Finally, the melt is atomized by gas and dried to obtain aluminum alloy powder for additive manufacturing.

8. A method for preparing aluminum alloy powder for additive manufacturing according to claim 7, characterized in that, Specifically, it includes the following steps; (1) Pure Al ingots, Al-Si, Al-Cu, Al-Mg, Al-Ti, Al-Y, Al-Sc, Al-Zr, and Al-V master alloys are added to the melting crucible according to the above-mentioned element mass percentages; (2) Inert gas is introduced into the melting crucible to form a protective atmosphere. The melting crucible is then heated to 730~750℃ and mechanically stirred to melt the pure Al ingot and all intermediate alloys. B4C powder and graphite powder are then added while mechanically stirring, and electromagnetic stirring is turned on for 10~15 minutes to disperse them evenly. The mechanical stirring is then turned off, and electromagnetic stirring is continued for 5~10 minutes to obtain a uniform melt. (3) The uniform melt is transferred into the intermediate ladle crucible under an inert gas atmosphere, and then flows into the atomization chamber through the zirconia guide tube. At the same time, high-pressure inert gas is injected for atomization and powder making. The airflow is classified to obtain powder with a size of 15~53μm. The powder is dried with inert gas to obtain aluminum alloy powder for additive manufacturing.

9. A method for preparing aluminum alloy powder for additive manufacturing according to claim 8, characterized in that, The mechanical stirring speed is 300~500 rpm; the electromagnetic stirring frequency is 50~100 Hz.

10. A method for preparing aluminum alloy powder for additive manufacturing according to claim 8, characterized in that, The inert gas is argon or helium with a purity of 99.999%; the pressure of the high-pressure inert gas is 2.5~4.0 MPa.

Citation Information

Patent Citations

  • High-toughness cast aluminum-silicon alloy and preparation method thereof

    CN114717453A

  • In-situ ceramic skeleton reinforced heat-resistant aluminum alloy material and preparation method thereof

    CN121161089A